Lihuaxuella thermophila gen. nov., sp. nov., isolated from a geothermal soil sample in Tengchong, Yunnan, south-west China - Tian-Tian Yu; Bing-Huo Zhang; Ji-Cheng Yao; Shu-Kun Tang; En-Min Zhou; Yi-Rui Yin; Da-Qiao Wei; Hong Ming; Wen-Jun Li (Antonie van Leeuwenhoek, 2012)

Combined effect of sCD40L and PI3K siRNA on transplanted tumours growth and microenvironment in nude mice with gastric cancer - Rui Li; Wei-Chang Chen; Xue-Qin Pang; Wen-Yan Tian; Wei-Peng Wang; Xue-Guang Zhang (Molecular Biology Reports, 2012)

CD40 signal expression in gastric cancer tissue and its correlation with prognosis of gastric cancer patients - Rui Li; Wei-Chang Chen; Xue-Qin Pang; Wen-Yan Tian; Wei-Peng Wang; Xue Guang Zhang (Molecular Biology Reports, 2012)

Increased expression of calcium-sensing receptors in atherosclerosis confers hypersensitivity to acute myocardial infarction in rats - Jin Guo; Hong-zhu Li; Lu-chuan Wang; Wei-hua Zhang; Guang-wei Li; Wen-jing Xing; Rui Wang; Chang-qing Xu (Molecular and Cellular Biochemistry, 2012)

Effects of Danggui Buxue Tang, a traditional Chinese herbal decoction, on high glucose-induced proliferation and expression of extracellular matrix proteins in glomerular mesangial cells - Hao-Liang Ke; Ying-Wen Zhang; Bi-Fa Zhou; Rui-Tang Zhen (Natural Product Research, 2012)

Gastric cancer cell lines AGS before and after CD40 signal activating - Rui Li; Xue-Qin Pang; Wei-Chang Chen; Ling Li; Wen-Yan Tian; Xue-Guang Zhang (Molecular Biology Reports, 2012)

Novel HMW glutenin genes from Aegilops tauschii and their unique structures - Wen-Jie Chen; Zhong-Wei Yuan; Lian-Quan Zhang; Xing Fan; Ze-Hong Yan; Ji-Rui Wang; You-Liang Zheng; Huai-Gang Zhang; Deng-Cai Liu (Genes & Genomics, 2012)

Determination of Geometrical and Structural Representative Volume Elements at the Baihetan Dam Site - Wen Zhang; Jian-ping Chen; Chang Liu; Rui Huang; Ming Li; Ying Zhang (Rock Mechanics and Rock Engineering, 2012)

Gene expression profiling of Sinapis alba leaves under drought stress and rewatering growth conditions with Illumina deep sequencing - Cai-Hua Dong; Chen Li; Xiao-Hong Yan; Shun-Mou Huang; Jin-Yong Huang; Li-Jun Wang; Rui-Xing Guo; Guang-Yuan Lu; Xue-Kun Zhang; Xiao-Ping Fang; Wen-Hui Wei (Molecular Biology Reports, 2012)

Chemical composition and antioxidant activities of extracts from Apocyni Veneti Folium - Sui-Hong Yan; Ying-Yong Zhao; Hai-Song Zeng; Yongmin Zhang; Rui-Chao Lin; Wen-Ji Sun (Natural Product Research, 2012)

Temperature reconstruction from tree-ring maximum latewood density of Qinghai spruce in middle Hexi Corridor, China - Feng Chen; Yu-jiang Yuan; Wen-shou Wei; Shu-long Yu; Zi-ang Fan; Rui-bo Zhang; Tong-wen Zhang; Qin Li; Hua-ming Shang (Theoretical and Applied Climatology, 2012)

Metagenomic analysis of DNA viruses in a wastewater treatment plant in tropical climate - Hideyuki Tamaki; Rui Zhang; Florent E. Angly; Shota Nakamura; Pei‐Ying Hong; Teruo Yasunaga; Yoichi Kamagata; Wen‐Tso Liu (Environmental Microbiology, 2012)
Summary Viruses have been detected in the different stages of wastewater treatment plants (WWTPs) at concentrations of 10 8 –10 10 ml −1 of virus‐like particles (VLPs), 10–1000 times higher than in natural aquatic environments, suggesting that WWTPs can be considered as an important reservoir and source of viruses. This study revealed novel diversity and function with the DNA viral communities in the influent, activated sludge, anaerobic digester, and effluent of a domestic WWTP using metagenomics. WWTP was a very specific environment, with less than 5% of the > 936 000 metagenomic sequences obtained (∼70–119 Mbp per sample) similar to sequences present in other environmental viromes. Many viruses found in the WWTP were novel, resulting in only 82% were shared. These data suggested that VLPs of most viral types could be present between 1 and 30 days in the process before they were discharged. Viruses in WWTP and the discharged ones can have potential impacts on the functioning of the wastewater treatment system and on the dynamics of microbial community in the surrounding aquatic environments respectively.